Effects of age on hypoxic tolerance in women - Tom Citherlet; Antoine Raberin; Giorgio Manferdelli; Grégoire Millet (Bern Open Publishing, 2023)
Introduction The prevalence of acute mountain sickness (AMS) is increasing with altitude (i.e., 10-25% at 2,500 m and 50-85% at ~ 5,000 m; Bärtsch & Swenson, 2013). While there is no error-free test to predict its occurrence, several risk factors and tests have been proposed. For example, the hypoxic ventilatory response (HVR) measures the ratio between the increase in ventilation (VE) and the decrease in pulse saturation (SpO2) during hypoxic exposure. Some studies reported an increased (Lhuissier et al., 2012), no difference (Pokorski and Marczak, 2003), or a decreased HVR (Kronenberg and Drage, 1973) with age. The effect of sex remains also debated since women have been reported to have a higher (Richalet et al., 2012) or lower (Schneider et al. 2002; Vardy et al., 2006) AMS prevalence. Therefore, we aimed to compare measurements of HVR, VE and SpO2 between pre- (PreM) and post-menopausal (postM) women and to investigate if they are related to AMS. We hypothesized differences in hypoxic tolerance between age groups. Methods We screened pre-menopausal women (PreM; n = 13; age = 31.7 ± 7.8yr; weight = 63.5 ±9.6 kg; height = 167 ±10 cm) during three phases (early follicular, Fol1; late follicular, Fol2; luteal, Lut3) of their menstrual cycle and post-menopausal women (PostM; n = 15; age = 62.8 ±2.3 yr; weight = 56.1 ±8.3 kg; height 163 ±5 cm) on one occasion. They were evaluated with a pure nitrogen breathing test (N2T; Solaiman et al., 2014) for HVR and with a cycling exercise (5 min of rest followed by 5 min of cycling at 1.5 W/kg) in hypoxia (FiO2 = 14%; simulated altitude of 3,500 m) with measurement of SpO2 and VE. They were then exposed to one night in real altitude (3,375 m) with AMS assessment (Lake Louise Score; Roach et al., 2018). Results PreM had a higher resting VE in normoxia (9.95-10.07 vs 8.50 L/min; P < 0.05) and increased VE (7.49-8.78 vs 5.41 L/min; P < 0.05) during the N2T at the three measurements points than PostM. Moreover, only at Fol2, HVR (-0.43 vs -0.27 L/min/%; P = 0.023), VEpeak (18.9 vs 15.0 L/min; P = 0.025) during N2T and resting SpO2 in normoxia (95.9 vs 94.9, P = 0.093) were higher in PreM. The prevalence of AMS was similar between PreM and PostM (30.8 vs 40.0%). When AMS positive and AMS negative subgroups were compared, no difference in HVR was found while there were differences in SpO2 and VE. Discussion/Conclusion The main finding of the present study is that HVR was higher in PreM than in PostM only during the late follicular phase of the former. Since estrogen is known to have a stimulatory effect on both pulmonary ventilation and blood vessel vasodilation and peaks during this phase, this suggests that it is the main trigger of the observed differences in HVR. The prevalence of AMS was in line with the literature for a similar altitude (34% at 3,650m; Maggiorini et al., 1990). Contrary to Richalet et al. (2012), HVR did not diagnose AMS in any group nor was lower in the older age group. No other parameter showed to be a solid predictive metric for AMS. Given conflicting results in this study (i.e., HVR and AMS) and in the literature, there is no clear evidence of an effect of age on hypoxic tolerance and on AMS prediction. References Bärtsch, P., & Swenson, E. R. (2013). Acute high-altitude illnesses. New England Journal of Medicine, 368(24), 2294-2302. https://doi.org/10.1056/NEJMcp1214870 Kronenberg, R. S., & Drage, C. W. (1973). Attenuation of the ventilatory and heart rate responses to hypoxia and hypercapnia with aging in normal men. The Journal of Clinical Investigation, 52(8), 1812-1819. https://doi.org/10.1172/JCI107363 Lhuissier, F. J., Canouï‐Poitrine, F., & Richalet, J. P. (2012). Ageing and cardiorespiratory response to hypoxia. The Journal of Physiology, 590(21), 5461-5474. https://doi.org/10.1113/jphysiol.2012.238527 Maggiorini, M., Bühler, B., Walter, M., & Oelz, O. (1990). Prevalence of acute mountain sickness in the Swiss Alps. British Medical Journal, 301(6756), 853-855. https://doi.org/10.1136/bmj.301.6756.853 Pokorski, M., & Marczak, M. (2003). Ventilatory response to hypoxia in elderly women. Annals of Human Biology, 30(1), 53-64. https://doi.org/10.1080/03014460210162000 Richalet, J. P., Larmignat, P., Poitrine, E., Letournel, M., & Canouï-Poitrine, F. (2012). Physiological risk factors for severe high-altitude illness: A prospective cohort study. American Journal of Respiratory and Critical Care Medicine, 185(2), 192-198. https://doi.org/10.1164/rccm.201108-1396OC Roach, R. C., Hackett, P. H., Oelz, O., Bärtsch, P., Luks, A. M., MacInnis, M. J., ... & Lake Louise AMS Score Consensus Committee. (2018). The 2018 Lake Louise acute mountain sickness score. High Altitude Medicine & Biology, 19(1), 4-6. https://doi.org/10.1089/ham.2017.0164 Schneider, M., Bernasch, D., Weymann, J., Holle, R., & Bärtsch, P. (2002). Acute mountain sickness: influence of susceptibility, preexposure, and ascent rate. Medicine & Science in Sports & Exercise, 34(12), 1886-1891. Solaiman, A. Z., Feehan, R. P., Chabitnoy, A. M., Leuenberger, U. A., & Monahan, K. D. (2014). Ventilatory responses to chemoreflex stimulation are not enhanced by angiotensin II in healthy humans. Autonomic Neuroscience, 183, 72-79. https://doi.org/10.1016/j.autneu.2014.01.010 Vardy, J., Vardy, J., & Judge, K. (2006). Acute mountain sickness and ascent rates in trekkers above 2500 m in the Nepali Himalaya. Aviation, Space, and Environmental Medicine, 77(7), 742-744.